Post reunification economic fluctuations in Germany: A real business cycle interpretation - Michael A. Flor (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
We consider the cyclical properties of the German economy prior and after reunification in 1990 from the perspective of a real business cycle model. The model provides the framework for the selection and consistent measurement of the variables whose time series properties characterize the cycle. Simulations of the calibrated model reveal the model's potential to interpret the data. Major findings are that: i) the volatility of most aggregate time series has not changed significantly between the two time periods, ii) despite many conceptual differences between the European and the U.S. System of Accounts, the calibrated parameter values for the German economy are within the range of values usually employed in the real business cycle literature, iii) the model is closer to the data for the time period prior to reunification.
Keywords: C82; E01; E32; 330; Macroeconomic Data; Measurement and Data on National Income and Product Accounts; Economic Fluctuations; Real Business Cycles